Regeneration method of cement stabilized macadam layer reclaimed material, regenerated mixture and application
By mixing the cement-stabilized gravel layer milling recovery material with new gravel aggregate and increasing the content of fine aggregate and cement in the graded recycled mixture, the problems of unstable quality and poor performance of the recycling of cement-stabilized gravel layer recycling materials in the prior art are solved, and efficient and economical recycling of the graded gravel base layer is achieved.
Patent Information
- Application Number
- CN202411529881.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the recycling method for milling and planing recycling materials of cement stable gravel layer in milling and planing in the milling and planing of cement has problems such as unstable quality, limited economic transportation distance, and the performance of the new base layer is not as good as that of the old base layer.
The cement-stabilized gravel layer milling and planing recovery material is used to mix it with the new gravel aggregate, and the proportion of grading regenerated mixture is determined through multi-stage screening, and the content of fine aggregates and cement is increased to form a grading regenerated mixture that meets the target grading range.
The construction performance and mechanical indicators of the graded recycled mixture are improved, the strength and crack resistance of the newly produced graded gravel base layer are ensured, and the efficient recycling of cement-stable gravel layer recycling materials are achieved.
Smart Images

Figure BDA0005110223130000101 
Figure BDA0005110223130000111 
Figure BDA0005110223130000112
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of resource recycling, and in particular to a regeneration method, a regenerated mixture and an application of recycled materials from a cement-stabilized crushed stone layer. Background Art
[0002] In road construction, a cement-stabilized gravel base uses cement as the primary binder, along with crushed stone as the aggregate, and an appropriate amount of water. The base structure is then formed through paving and compaction. This structure primarily consists of aggregate (graded gravel) and mortar (water and a binder, which consists of cement and other mixed materials). It combines the bonding properties of cement with the mechanical properties of gravel to create a high-strength and stable base. Cement-stabilized gravel bases offer high stiffness, excellent load-spreading capabilities, and a certain degree of flexural strength, making them a semi-rigid base. They maintain good integrity under load and avoid excessive deformation. Furthermore, they exhibit excellent water stability, effectively resisting erosion and damage from moisture. However, due to the drying and temperature shrinkage of cement-stabilized gravel, cracks are prone to form during use. Insufficient base strength, poor construction quality, and uneven roadbed settlement can also contribute to cracks.
[0003] If the cement-stabilized gravel layer is damaged, it needs to be excavated and rebuilt. This is usually done using a milling machine, which takes up space for storage. The milled material from the cement-stabilized gravel layer not only takes up land but can also cause serious environmental pollution. Recycling the cement-stabilized gravel layer can avoid environmental pollution and conserve sand and gravel resources.
[0004] At present, there are four main methods for recycling the recycled materials from cement-stabilized gravel layers: (1) Concrete preparation. The recycled materials contain cement, sand, gravel and slag. After mixing with fresh cement, aggregate and slag, they can be made into environmentally friendly concrete that meets the performance requirements of ordinary cement concrete. The specific steps are to crush, screen and remove impurities from the recycled materials, mix and stir them with new materials in proportion, and then form and cure them into concrete products. (2) Recycled aggregate. The recycled materials are crushed into fragments of different particle sizes and can be used as aggregate for building concrete. Their performance is equivalent to that of ordinary aggregates, but they can reduce the consumption of natural aggregates and save resources. In actual applications, the quality of recycled aggregates must be strictly controlled and tested to ensure that they meet the performance standards of concrete aggregates. (3) Roadbed filling. The recycled materials are crushed into small particles and mixed with soil, and evenly laid on the roadbed, which can achieve the effect of filling, extend the service life of the road, and reduce the impact of the waste cement-stabilized gravel layer on the environment. During construction, the proportion and compaction degree of the mixture must be controlled to ensure the stability and bearing capacity of the roadbed. (4) Cold recycling technology. Specialized equipment is used to crush the existing cement-stabilized crushed stone layer on-site. Regeneration agents, cement, and coarse aggregate are then added, mixed, and compacted to form a new base layer. This technology fully utilizes raw materials, reduces transportation and disposal costs, and shortens the construction cycle. In actual application, the appropriate regeneration agent and construction process parameters should be selected based on the specific conditions and design requirements of the road.
[0005] However, the currently widely used recycling method for cement-stabilized crushed stone milling has the following drawbacks: First, the fine aggregate and cement paste in the cement-stabilized crushed stone milling are adhered to each other, and cement paste also adheres to the surface of the coarse aggregate, resulting in screening results that do not accurately reflect the actual gradation. As a result, the quality of concrete produced using this recycled material is unstable. Concrete is usually used in important structures. This has led to its current use in concrete production only in a small number of pilot projects, and large-scale application has not yet been achieved. Using cement-stabilized crushed stone milling recycled material to produce cement-stabilized macadam also suffers from inconsistent quality, which affects the service life of the new pavement. Second, from a technical perspective, the use of cement-stabilized crushed stone milling recycled material for roadbed filling is feasible. However, due to the low cost and high demand for roadbed filling materials, the economic transportation distance is limited, making it often economically unfeasible. The amount of cement-stabilized crushed stone milling recycled material used is also limited. Finally, for cracked and damaged base layers, a new base layer is formed by crushing it in situ, adding cement and coarse aggregate, mixing, and compacting it. However, due to the problems with the original base layer, the performance of this cold-recycled new base layer is often inferior to the old base layer, and its service life is also unreliable. Therefore, although there are currently various methods for recycling recycled materials from cement-stabilized crushed stone layers, these methods are mainly in the pilot stage and have not yet been widely promoted and applied.
[0006] Therefore, it is urgent to develop a regeneration method, graded recycled mixture and application of cement-stabilized crushed stone layer recycled materials to address the shortcomings of existing technologies. Summary of the Invention
[0007] The technical problem to be solved by the present invention is to provide a regeneration method, a regenerated mixture and an application of cement-stabilized crushed stone layer reclaimed material. The purpose is to use the cement-stabilized crushed stone layer milling reclaimed material mixed with crushed stone to generate a graded regenerated mixture.
[0008] The technical solution of the present invention to solve the above technical problems is as follows:
[0009] In a first aspect, a method for regenerating recycled material from a cement-stabilized crushed stone layer comprises the following steps:
[0010] (1) Gradation detection:
[0011] Taking the cement-stabilized crushed stone layer milling and recycling material, screening it and calculating the individual screening rate, cumulative screening rate and pass percentage of the cement-stabilized crushed stone layer milling and recycling material to obtain the gradation of the cement-stabilized crushed stone layer milling and recycling material;
[0012] Taking 30mm-50mm, 10mm-30mm, and 5mm-10mm new crushed stone aggregates, screening them and calculating the individual screening rate, cumulative screening rate, and passing percentage of the new crushed stone aggregates to obtain the gradation of the new crushed stone aggregates;
[0013] Taking fine aggregate of 0 mm to 5 mm, screening and calculating the individual sieve residue rate, cumulative sieve residue rate and pass percentage of the fine aggregate to obtain the gradation of the fine aggregate;
[0014] (2) Preparation of graded recycled mixture:
[0015] According to the gradation of the milling recycled material of the cement stabilized crushed stone layer, the gradation of the new crushed stone aggregate and the gradation of the fine aggregate obtained in step (1), the mixed weight ratio of the milling recycled material of the cement stabilized crushed stone layer, the new crushed stone aggregate and the fine aggregate is calculated until a graded recycled mixture within the target gradation range is obtained.
[0016] On the basis of the above technical solution, the present invention can also be improved as follows.
[0017] Furthermore, in the gradation test of step (1), the screening of the milling recovery material of the cement-stabilized crushed stone layer, the screening of the new crushed stone aggregate, and the screening of the fine aggregate all adopt multi-stage screening.
[0018] Furthermore, the sieve specifications used in the multi-stage screening include 0.075mm standard sieve, 0.3mm standard sieve, 0.6mm standard sieve, 1.18mm standard sieve, 2.36mm standard sieve, 4.75mm standard sieve, 9.5mm standard sieve, 13.2mm standard sieve, 16mm standard sieve, 19mm standard sieve, 26.5mm standard sieve, 31.5mm standard sieve, 37.5mm standard sieve and 53mm standard sieve.
[0019] Furthermore, step (2) includes the following specific steps:
[0020] (2-1) calculating the weight ratio of the recycled material from the milling of the cement-stabilized crushed stone layer, the recycled material from the milling of the cement-stabilized crushed stone layer, the recycled material from the new crushed stone aggregate, and the recycled material from the fine aggregate based on the target gradation range, the gradation of the recycled material from the milling of the cement-stabilized crushed stone layer, the recycled material from the new crushed stone aggregate, and the recycled material from the fine aggregate to obtain a graded recycled mixture;
[0021] (2-2) performing multi-stage screening on the graded recycled mixture obtained in (2-1), calculating the individual sieve residue rate, cumulative sieve residue rate, and pass percentage of the graded recycled mixture, and obtaining the gradation of the graded recycled mixture;
[0022] (2-3) If the gradation of the graded recycled mixture is within the target gradation range, it means that the preparation of the graded recycled mixture is qualified; if the gradation of the graded recycled mixture is not within the target gradation range, repeat steps (2-1) and (2-3) until a graded recycled mixture within the target gradation range is obtained.
[0023] Furthermore, the mass percentage of the graded recycled mixture within the target gradation range passing through the sieve holes is as follows: 100% for 53mm sieve hole, 75%-98% for 37.5mm sieve hole, 40%-60% for 19mm sieve hole, 25%-40% for 9.5mm sieve hole, 20%-35% for 4.75mm sieve hole, 15%-25% for 2.36mm sieve hole, 5%-10% for 0.6mm sieve hole, and 0%-5% for 0.075mm sieve hole.
[0024] In the second aspect, the graded recycled mixture is prepared by the regeneration method.
[0025] Furthermore, the maximum nominal particle size of the graded recycled mixture is 53 mm.
[0026] Furthermore, the fine aggregate in the graded recycled mix accounts for 10%-20% by weight of the graded recycled mix. If the 0mm-5mm machine-made sand content is less than 10%, severe segregation will still occur during paving. However, when its content exceeds 10%, segregation is significantly improved, and the improvement gradually increases with increasing content. Since both 0mm-5mm machine-made sand and cement-stabilized crushed stone milling reclaimed material are primarily fine material, increasing the 0mm-5mm fine aggregate content will inevitably reduce the amount of cement-stabilized crushed stone milling reclaimed material used. For economic reasons, the 0mm-5mm fine aggregate content should not exceed 20%.
[0027] Adding cement to graded recycled mixture can further improve the cohesion between aggregates and enhance the adsorption of aggregates.
[0028] Furthermore, the graded recycled mixture also includes cement, which accounts for 2% to 2.5% by weight of the graded recycled mixture. A higher cement content improves segregation, but pilot project experience shows that when the cement content exceeds 2.5%, the graded crushed stone base exhibits semi-rigid material properties. While the load-bearing capacity is improved, the crack resistance is significantly reduced. Therefore, the upper limit of the cement content is set at 2.5%.
[0029] The third aspect is the application of graded recycled mixture, which is used as the pavement base and subbase of the road.
[0030] Furthermore, the moisture content of the graded recycled mixture is increased by 2% based on the optimal moisture content. The optimal moisture content of cement-stabilized graded crushed stone is generally controlled to be between 4% and 8%, with the specific value determined based on actual construction conditions, raw material properties, and experimental data. To ensure the optimal moisture content of the mixture, the optimal value is typically determined through testing and appropriately adjusted based on site conditions. The optimal moisture content in the present invention is determined through testing, primarily considering that at this moisture content, the strength of the cement-stabilized crushed stone is optimized while avoiding cracking and fracture.
[0031] The moisture content of the graded recycled mix is increased by 2% from the optimal moisture content. Because the fine and coarse aggregates in the milled recycled material from the cement-stabilized crushed stone layer have weak adhesion, the cement-stabilized graded crushed stone mixed with the milled recycled material from the cement-stabilized crushed stone layer is prone to segregation during the paving process. Properly increasing the moisture content of the graded recycled mix can improve the adhesion of the coarse and fine aggregates in the cement-stabilized graded crushed stone, reduce segregation during paving, and ensure construction quality.
[0032] Principle of the present invention:
[0033] As time goes by, the original cement may undergo carbonization, weathering or other chemical reactions, resulting in a decrease in its bonding ability; during the recycling and regeneration process, the aggregate may be mechanically damaged, thereby changing its strength and particle size distribution, affecting the mechanical properties of the overall material; in addition, during the recycling process, the material may be mixed with some impurities or pollutants (such as soil, asphalt residue, etc.), and these impurities will weaken the performance of the recycled material. Therefore, the performance of the recycled material of the cement-stabilized gravel base is lower than that of the new material. The performance and quality of cement-stabilized gravel made from recycled materials are not as good as those produced from new materials.
[0034] A graded crushed stone base is formed by crushing, screening, and grading natural stone according to specific sieve sizes, then mixing the different grades of crushed stone in specific proportions, laying them to the designed thickness, and compacting them. Composed of crushed stone of varying particle sizes and without cement or other binders, it is a flexible base. This material exhibits excellent water permeability, quickly draining moisture from the base, preventing damage caused by moisture accumulation and making it less susceptible to thermal and drying shrinkage cracking. It effectively suppresses cracking caused by temperature fluctuations or water evaporation; it exhibits strong resistance to reflective cracking, and when used as the "inverted structure" of a composite pavement, it can significantly reduce the reflection of cracks from the semi-rigid base layer to the asphalt surface. It also exhibits strong adaptability, exhibiting good deformation tolerance, helping to alleviate stress concentration in the pavement's structural layers.
[0035] The strength of a graded crushed stone base primarily stems from the inter-aggregate interlocking force and internal friction. Through a well-designed gradation, crushed stone particles of varying sizes are tightly interlocked, forming a stable skeleton structure. This interlocking effect not only enhances the overall strength of the base but also helps resist damage from external loads. Friction is generated during contact and movement between crushed stone particles. The large contact area and numerous contact points between the particles generate significant internal friction, enhancing the base's overall stability and shear strength.
[0036] This invention uses 30mm-50mm crushed stone as the coarse aggregate and recycled material from the cement-stabilized crushed stone layer as the medium-sized aggregate. Because the recycled material from the cement-stabilized crushed stone layer has a large particle size dispersion, 10mm-30mm and 5mm-10mm crushed stone are added to adjust the gradation of the mixture. By mixing 30mm-50mm crushed stone, 10mm-30mm crushed stone, and 5mm-10mm crushed stone with the recycled material from the cement-stabilized crushed stone layer in a specific proportion, a graded crushed stone mixture that meets gradation requirements can be formed.
[0037] Mechanical analysis and engineering practice have shown that increasing the maximum nominal aggregate size can improve the shear strength of the graded crushed stone layer, thereby reducing pavement deformation. The maximum nominal aggregate size of a conventional graded crushed stone layer is 37.5 mm. To enhance this shear strength, the present invention uses a graded crushed stone mixture made from 30 to 50 mm crushed stone and recycled milling material from a cement-stabilized crushed stone layer, increasing the maximum aggregate size to 53 mm. This offsets the adverse effects of the poor aggregate uniformity and reduced mechanical properties of the recycled milling material from the cement-stabilized crushed stone layer on the strength of the newly produced graded crushed stone.
[0038] Although the bearing capacity of the graded crushed stone base was significantly improved after increasing the maximum aggregate size to 53 mm, severe segregation of the graded crushed stone was observed during paving. Analysis revealed that the increased particle size significantly increased the difference in gravitational properties between the larger aggregate and the finer aggregate. Furthermore, the finer aggregate in the graded crushed stone primarily came from recycled material from the cement-stabilized crushed stone layer, which has poorer adsorption properties than new fine aggregates such as machine-made sand. These two factors combined led to severe segregation in the graded crushed stone. Adding fine aggregate to the graded recycled mix improves cohesion and enhances aggregate adsorption.
[0039] Beneficial effects of the present invention:
[0040] (1) The present invention uses new crushed stone aggregate and cement-stabilized crushed stone layer milling and recycling materials to produce graded crushed stone mixture, and increases the maximum nominal particle size of the graded crushed stone mixture aggregate to 53 mm, thereby offsetting the adverse effects of poor aggregate uniformity and decreased mechanical properties of the cement-stabilized crushed stone layer milling and recycling materials on the strength of the newly produced graded crushed stone, so that the various mechanical indicators of the graded crushed stone base produced using the cement-stabilized crushed stone layer milling and recycling materials meet the requirements of the specifications;
[0041] (2) The present invention ensures that the graded recycled mixture has particularly good workability by ensuring that the content of 0mm-5mm fine aggregate and cement in the graded recycled mixture is sufficient; the cement content of 2%-2.5% can improve the workability of the graded crushed stone and increase the strength of the graded crushed stone base without reducing the anti-cracking ability of the graded crushed stone base;
[0042] (3) In the graded recycled mixture of the present invention, the proportion of the milled recycled materials of the cement-stabilized crushed stone layer reaches 30%-40%. In the major repair of road projects, 30%-40% of the milled recycled materials of the cement-stabilized crushed stone layer can be reused, thereby reducing the occupied area. DETAILED DESCRIPTION
[0043] The principles and features of the present invention are described below. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Where specific techniques or conditions are not specified in the examples, the techniques or conditions described in the literature in this field or the product instructions are used. Where the manufacturers of the reagents or instruments used are not specified, they are all conventional products that can be purchased through regular channels.
[0044] As a non-uniform, dispersed material system, graded crushed stone effectively absorbs concentrated stress at the crack tips of the underlying stratum, thereby reducing the occurrence of reflective cracks in the overlay. Furthermore, due to its excellent water stability, it is widely used in pavement structures. However, the poor aggregate uniformity of recycled milling material in cement-stabilized crushed stone layers leads to reduced mechanical properties. Therefore, using this as raw material for graded crushed stone production results in inferior performance compared to graded crushed stone produced using new raw materials.
[0045] Therefore, in order to improve its shear strength, compared with the maximum nominal particle size of 37.5mm of the traditional graded crushed stone layer, the present invention uses 30mm-50mm new crushed stone aggregate and cement-stabilized crushed stone layer milling recycled material to produce graded crushed stone mixture, and increases the maximum nominal particle size of the recycled graded crushed stone mixture aggregate to 53mm, thereby offsetting the adverse effects of poor uniformity and decreased mechanical properties of the cement-stabilized crushed stone layer milling recycled material aggregate on the strength of the newly produced graded crushed stone.
[0046] Since the cement slurry in the milled recycled material of the cement-stabilized crushed stone layer has already completed the hydration reaction, the adsorption between the coarse aggregate and the fine powder in the graded recycled mixture made by adding new crushed stone aggregate is poor, which leads to easy segregation during transportation and paving. Especially during paving, the newly prepared graded recycled mixture will show significant segregation, with the fine powder concentrated in the middle of the road surface and the coarse aggregate gathered on both sides; in addition, after the maximum particle size of the aggregate increases to 50mm, the difference in gravity properties of the coarse and fine aggregates in the mixture increases, further aggravating the segregation phenomenon and seriously affecting the construction quality of the graded crushed stone base of the road. Therefore, in order to improve the adsorption performance between aggregates in the graded recycled mixture and reduce the segregation phenomenon during transportation and paving, the present invention adds a certain amount of cement, 10mm-30mm crushed stone, 5mm-10mm crushed stone and 0mm-5mm fine aggregate to the graded recycled mixture to form a graded crushed stone mixture that meets the grading requirements.
[0047] This embodiment relates to a method for regenerating recycled material from a cement-stabilized crushed stone layer, comprising the following steps:
[0048] (1) Gradation detection:
[0049] Taking the cement-stabilized crushed stone layer milling and recycling material, screening it and calculating the individual screening rate, cumulative screening rate and pass percentage of the cement-stabilized crushed stone layer milling and recycling material to obtain the gradation of the cement-stabilized crushed stone layer milling and recycling material;
[0050] Taking 30mm-50mm, 10mm-30mm, and 5mm-10mm new crushed stone aggregates, screening them and calculating the individual screening rate, cumulative screening rate, and passing percentage of the new crushed stone aggregates to obtain the gradation of the new crushed stone aggregates;
[0051] Taking fine aggregate of 0 mm to 5 mm, screening and calculating the individual sieve residue rate, cumulative sieve residue rate and pass percentage of the fine aggregate to obtain the gradation of the fine aggregate;
[0052] (2) Preparation of graded recycled mixture:
[0053] According to the gradation of the milling recycled material of the cement stabilized crushed stone layer, the gradation of the new crushed stone aggregate and the gradation of the fine aggregate obtained in step (1), the mixed weight ratio of the milling recycled material of the cement stabilized crushed stone layer, the new crushed stone aggregate and the machine fine aggregate is calculated until a graded recycled mixture within the target gradation range is obtained.
[0054] In this embodiment, preferably, in the gradation test of step (1), the screening of the cement-stabilized crushed stone layer milling recovery material, the screening of the new crushed stone aggregate, and the screening of the fine aggregate all adopt multi-stage screening. The sieve specifications adopted in the multi-stage screening include 0.075mm standard sieve, 0.3mm standard sieve, 0.6mm standard sieve, 1.18mm standard sieve, 2.36mm standard sieve, 4.75mm standard sieve, 9.5mm standard sieve, 13.2mm standard sieve, 16mm standard sieve, 19mm standard sieve, 26.5mm standard sieve, 31.5mm standard sieve, 37.5mm standard sieve, and 53mm standard sieve.
[0055] In this embodiment, step (2) preferably includes the following specific steps:
[0056] (2-1) calculating the weight ratio of the recycled material from the milling of the cement-stabilized crushed stone layer, the recycled material from the milling of the cement-stabilized crushed stone layer, the recycled material from the new crushed stone aggregate, and the recycled material from the fine aggregate based on the target gradation range, the gradation of the recycled material from the milling of the cement-stabilized crushed stone layer, the recycled material from the new crushed stone aggregate, and the recycled material from the fine aggregate to obtain a graded recycled mixture;
[0057] (2-2) performing multi-stage screening on the graded recycled mixture obtained in step (2-1), calculating the individual sieve residue rate, cumulative sieve residue rate, and pass percentage of the graded recycled mixture, and obtaining the gradation of the graded recycled mixture;
[0058] (2-3) If the gradation of the graded recycled mixture is within the target gradation range, it means that the preparation of the graded recycled mixture is qualified; if the gradation of the graded recycled mixture is not within the target gradation range, repeat steps (2-1) and (2-3) until a graded recycled mixture within the target gradation range is obtained.
[0059] Among them, the mass percentage of the graded recycled mixture within the target gradation range passing through the sieve holes is as follows: 53mm sieve hole 100%, 37.5mm sieve hole 75%-98%, 19mm sieve hole 40%-60%, 9.5mm sieve hole 25%-40%, 4.75mm sieve hole 20%-35%, 2.36mm sieve hole 15%-25%, 0.6mm sieve hole 5%-10%, 0.075mm sieve hole 0%-5%.
[0060] The calculation method of the present invention uses the weight percentages of the recycled material from the cement-stabilized crushed stone layer, new crushed stone aggregate, and fine aggregate as weights. The individual sieve retention rates, cumulative sieve retention rates, and pass percentages of these materials are multiplied by the corresponding weights and then added together to obtain the individual sieve retention rates, cumulative sieve retention rates, and pass percentages of the recycled aggregate. The weight ratio of the recycled aggregate sample to the coarse aggregate sample is continuously adjusted until the individual sieve retention rates, cumulative sieve retention rates, and pass percentages of the recycled aggregate fall within the target gradation range.
[0061] This embodiment also relates to a graded recycled mixture, which is prepared using the aforementioned recycling method.
[0062] In this embodiment, preferably, the maximum nominal particle size of the graded recycled mixture is 53 mm.
[0063] In this embodiment, the fine aggregate in the graded recycled mix preferably accounts for 10%-20% by weight of the graded recycled mix. If the 0mm-5mm fine aggregate content is less than 10%, severe segregation will still occur during paving. However, when its content exceeds 10%, segregation is significantly improved, and the improvement gradually increases with increasing content. Since both the 0mm-5mm fine aggregate and the recycled material from the milling of the cement-stabilized crushed stone layer are primarily fine material, increasing the 0mm-5mm fine aggregate content will inevitably reduce the amount of recycled material from the milling of the cement-stabilized crushed stone layer. For economic reasons, the 0mm-5mm fine aggregate content should not exceed 20%.
[0064] In this embodiment, the graded recycled mixture preferably further comprises cement, with the cement accounting for 2% to 2.5% by weight of the graded recycled mixture. Generally, a higher cement content improves segregation. However, based on pilot project experience, when the cement content exceeds 2.5%, the graded crushed stone base exhibits semi-rigid material properties. While the load-bearing capacity is improved, the crack resistance is significantly reduced. Therefore, the upper limit of the cement content is set at 2.5%.
[0065] This embodiment also relates to the application of graded recycled mixture, wherein the graded recycled mixture is used as a pavement base layer of a newly built road, a subbase layer of a newly built road, or a hard shoulder surface layer of a road.
[0066] Glossary:
[0067] Gradation is the distribution of aggregate particles at different particle sizes, which can be determined through sieving tests. Parameters that reflect aggregate gradation include the individual sieve retention percentage, the cumulative sieve retention percentage, and the passing percentage.
[0068] The sieve residue rate is the percentage of the sieve residue on a certain sieve to the total mass of the sample.
[0069] The cumulative sieve residue rate is the sum of the sieve residue percentage of a certain sieve and the sieve residue percentages of each sieve larger than that sieve.
[0070] The passing percentage is the percentage of the mass passing through a certain sieve to the total mass of the sample, that is, the difference between 100 and the cumulative residue on a certain sieve.
[0071] Maximum dry density: Graded crushed stone refers to stone with a certain particle size range obtained after being graded through a screen. Its characteristics are high density, good wear resistance, and strong resistance to weathering. Dry density refers to the volume-to-weight ratio of stone in a dry state. It is one of the important indicators of graded crushed stone performance and usually needs to be determined through experimental testing. The maximum dry density of the graded crushed stone base usually fluctuates within a range rather than a fixed value. According to publicly released information, the maximum dry density of graded crushed stone is roughly 2.220-2.50g / cm 3 Maximum dry density is a key quality control parameter during the construction of graded crushed stone, directly determining the degree of base compaction. Therefore, during construction, the crushed stone's particle size distribution, moisture content, and compaction method should be strictly controlled to ensure that the base compaction meets the design requirements.
[0072] Optimum Moisture Content: The moisture content of the mixture has a direct impact on the compaction of the cement-stabilized graded crushed stone base. Compaction tests have shown that, with varying moisture contents, the same mixture, under the same compaction work, will produce different degrees of compaction. Moisture content also significantly affects the strength of the graded crushed stone. An appropriate amount of moisture acts as a lubricant during the compaction process, promoting a tight bond between the crushed stone particles and thereby improving the strength of the structural layer.
[0073] The California Bearing Ratio (CBR), first proposed by the California State Highway Department, is an indicator for assessing the bearing capacity of subgrade and pavement materials. CBR is the ratio of the unit pressure applied to a test material at a penetration of 2.5 mm to the standard load strength of standard crushed stone at the same penetration. It is a relative percentage used to indicate the bearing capacity of subgrade or pavement materials.
[0074] In summary, the present invention uses new crushed stone aggregate and cement-stabilized crushed stone layer milling and recycling materials to produce graded crushed stone mixture, increasing the maximum nominal particle size of the graded crushed stone mixture aggregate to 53mm, thereby offsetting the adverse effects of poor aggregate uniformity and decreased mechanical properties of the cement-stabilized crushed stone layer milling and recycling materials on the strength of the newly produced graded crushed stone, so that the various mechanical indicators of the graded crushed stone base produced using the cement-stabilized crushed stone layer milling and recycling materials meet the specification requirements; the present invention ensures that the graded recycled mixture has particularly good construction performance by ensuring the content of 0mm-5mm fine aggregate and cement in the graded recycled mixture; in the present invention, the proportion of cement-stabilized crushed stone layer milling and recycling materials in the graded recycled mixture reaches 30%-40%. In the overhaul of road projects, 30%-40% of the cement-stabilized crushed stone layer milling and recycling materials can be reused, reducing the floor space occupied by the cement-stabilized crushed stone layer milling and recycling materials. The following further illustrates the present invention with specific embodiments.
[0075] A section of a national highway is 126 km long and was built in 1989. It was fully completed and opened to traffic in 1997-1998. The original road standard was low, mainly composed of a sand and gravel cushion layer + 25 cm graded crushed stone + a concrete surface layer of about 25 cm. In 2003, large-scale subsidence and road surface damage occurred, which were mainly treated by grouting stabilization. In 2005, some major repairs were carried out, using the "white + black" reinforcement plan (original concrete slab + 20-40 cm water-stabilized crushed stone + seal layer + 6 cm AC16 asphalt surface layer). In 2008, selected sections were successively carried out for medium and small repairs of the asphalt concrete pavement, including hot regeneration, cold regeneration, milling, and foam regeneration.
[0076] Years of maintenance and renovation have formed some unique pavement structures (concrete slab + semi-rigid water-stabilized base + asphalt surface layer); during this period, the old cement concrete pavement was also crushed, the cement stabilized layer was excavated, and the recycled cement stabilized layer was mixed with new materials and re-paved as the base layer, and then the asphalt concrete surface layer was paved on it.
[0077] The experimental research work and test road construction for overhaul will begin in 2021, and the section-by-section overhaul will be officially carried out in 2024.
[0078] The overhaul plan is as follows:
[0079] Step 1: Mill the water-stable gravel base and asphalt concrete pavement in layers and stack them in categories.
[0080] Step 2: Use the recycled material from the cement-stabilized crushed stone layer as raw material to produce a graded crushed stone mixture. The mix design steps are as follows:
[0081] (1) Sampling of cement-stabilized crushed stone layer milling recovery material: Three samples were taken in parallel, sieved, and the individual screening rate, cumulative screening rate, and pass rate were calculated to obtain the gradation of the cement-stabilized crushed stone layer milling recovery material sample (Table 1). The sieve specifications used in the multi-stage screening include 0.075mm standard sieve, 0.3mm standard sieve, 0.6mm standard sieve, 1.18mm standard sieve, 2.36mm standard sieve, 4.75mm standard sieve, 9.5mm standard sieve, 13.2mm standard sieve, 16mm standard sieve, 19mm standard sieve, 26.5mm standard sieve, 31.5mm standard sieve, 37.5mm standard sieve, and 53mm standard sieve.
[0082] Table 1 Screening of recycled materials from cement stabilized gravel layer milling
[0083]
[0084] (2) Gravel samples with sizes of 30 mm to 50 mm, 10 mm to 30 mm, and 5 mm to 10 mm were selected. Three samples were taken in parallel and then sieved. The individual sieve residues, cumulative sieve residues, and pass percentages were calculated to determine the gradation of the gravel samples (Tables 2, 3, and 4). The multi-stage sieve mesh sizes used included standard sieves of 0.3 mm, 0.6 mm, 1.18 mm, 2.36 mm, 4.75 mm, 9.5 mm, 13.2 mm, 16 mm, 19 mm, 26.5 mm, 31.5 mm, 37.5 mm, and 53 mm.
[0085] Table 2 Crushed stone screening table (5mm-10mm)
[0086]
[0087] Table 3 Crushed stone screening table (10mm-30mm)
[0088]
[0089] Table 4 Crushed stone screening table (30mm-50mm)
[0090]
[0091] (3) 0 mm to 5 mm machine-made sand was sampled and screened. Three samples were taken in parallel, and the individual screening ratios, cumulative screening ratios, and pass percentages were calculated to obtain the gradation of the 0 mm to 5 mm fine aggregate sample (Table 5). The sieve sizes used for the multi-stage screening in this step also included standard sieves of 0.3 mm, 0.6 mm, 1.18 mm, 2.36 mm, 4.75 mm, 9.5 mm, 13.2 mm, 16 mm, 19 mm, 26.5 mm, 31.5 mm, 37.5 mm, and 53 mm.
[0092] Table 5 Fine aggregate screening table (0mm-5mm)
[0093]
[0094] (4) Calculate the weight ratio of the recycled material from the cement-stabilized crushed stone layer, the grading of the 30mm-50mm and 10mm-30mm crushed stone samples, and the grading of the 0mm-5mm fine aggregate samples until a recycled aggregate sample that meets the target gradation range is obtained. The content of 0mm-5mm fine aggregate ranges from 10% to 20%. Target gradation range: The mass percentage of the graded recycled mixture within the target gradation range that passes through the sieve is as follows: 100% for 53mm sieve, 75%-98% for 37.5mm sieve, 40%-60% for 19mm sieve, 25%-40% for 9.5mm sieve, 20%-35% for 4.75mm sieve, 15%-25% for 2.36mm sieve, 5%-10% for 0.6mm sieve, and 0%-5% for 0.075mm sieve. See Tables 6 and 7.
[0095] Table 6 Passage rate of key sieve holes of graded crushed stone after mixing
[0096] Sieve size 0.075 0.6 2.36 4.75 9.5 19 37.5 53 Pass rate 3.3 10.6 22.4 32.7 43.7 52.9 93.2 100
[0097] Table 7 Blending ratio of different recycled materials
[0098] Recycled material dosage 0mm-5mm dosage 5mm-10mm dosage 10mm-30mm dosage 30mm-50mm dosage 40% 14.5% 2% 6.5% 37% 35% 16.5% 1.5% 17% 30% 30% 18% 5% 17% 30%
[0099] (5) According to the weight ratio of the cement-stabilized crushed stone layer milling recycled material, 30mm-50mm and 10mm-30mm crushed stone, 5mm-10mm and 0mm-5mm fine aggregate determined in step (4), a mixture is prepared and 2-2.5% of the total weight of cement is added.
[0100] (6) Test results
[0101] Compaction tests were conducted to determine the maximum dry density and optimum moisture content, which were 2.172 g / cm and 4% respectively. The California Bearing Ratio test was then conducted. For the California Bearing Ratio test, after forming the specimen at the maximum dry density and optimum moisture content, the specimen was placed in the center of a universal testing machine. Four 1.25 kg load plates were placed perpendicularly, with their central axes intersecting, around a 5 cm diameter cylindrical penetration rod at the top of the specimen. The universal testing machine was started, and the penetration rod was slowly penetrated into the specimen at a rate of 1 mm / min. When the penetration reached 2.5 cm and 5 cm, the corresponding peak forces were recorded and the larger of the two values was calculated before the test was terminated.
[0102] Table 8 California load ratio test results
[0103] 1 2 3 average 40% recycled materials 320.57% 402.98% 240.11% 321.22% 35% recycled materials 340.78% 420.68% 380.96% 380.81% 30% recycled materials 403.33% 450.32% 348.32% 400.66%
[0104] Three parallel California load ratio tests were conducted for each recycled content, and the test results are shown in Table 8. As shown in Table 8, the average value of the California load ratio test for specimens with 30%-40% recycled content was 321.22%, which is greater than 200%, meeting the regulatory requirements.
[0105] The milled recycled material in the cement-stabilized crushed stone layer contains a high content of fine aggregate. When preparing cement-stabilized graded crushed stone, a cement-stabilized crushed stone mixture that meets grading requirements can be prepared without adding 0mm-5mm machine-made sand. However, during paving on a test section, the cement-stabilized crushed stone mixture exhibited severe segregation, with coarse aggregate concentrated on the sides of the paved surface and fine aggregate and fine aggregate concentrated in the center. Research has shown that the fine aggregate in the milled recycled material in the cement-stabilized crushed stone layer has poor adsorption properties and, despite the addition of cement, did not mix well with the coarse aggregate. After repeated testing, the addition of 0mm-5mm machine-made sand to over 10% and the proportion of milled recycled material in the cement-stabilized crushed stone layer to below 50% were increased. Furthermore, the moisture content of the cement-stabilized crushed stone mixture during paving was increased by 2% from the optimal moisture content, resolving the segregation of coarse and fine aggregate during paving.
[0106] Step 3: Construction work
[0107] (1) Preparation:
[0108] ① Thoroughly clean and sweep the old road surface, applying water to keep it moist and prevent water from flowing. Clean the soil near the shoulder. ② Ensure that materials, machinery, personnel, and equipment are in place. ③ After cleaning the base, restore the left, center, and right piles on the old road. Construction will proceed at half the width, with one pile every 10 meters. Elevation control piles will be set up on both sides of the shoulder, followed by diagonal lines to ensure consistent thickness. ④ Base aggregates must be sorted and stacked. Fine aggregates must be placed in a shed or covered with colored strips (to keep them dry, dustproof, waterproof, and prevent secondary contamination of the site). Incoming aggregates must be tested before use.
[0109] (2) Mixing and transportation of mixture:
[0110] The graded gravel mixture is centrally mixed at the site, preferably using a 400-type or larger forced mixing plant for the large-size graded gravel base. After uniform mixing, it is transported to the construction site using dump trucks. Because gravel loses moisture during transportation, paving, and compaction, to ensure that the graded gravel on site is close to the optimal moisture content for compaction, the moisture content should be increased appropriately during mixing, typically above the optimal moisture content. The cement colloid in cement-stabilized graded gravel milling reclaimed material is porous and absorbs some moisture during mixing. Therefore, the moisture content can be increased by 2% in low and humid temperatures and by 3% in high and dry temperatures. Appropriately increasing the moisture content enhances the adsorption between coarse and fine aggregates and improves aggregate segregation during paving.
[0111] To prevent segregation of the mixed material during loading, a baffle should be installed between the conveyor belt and the feed port to reduce gravity-induced segregation of coarse and fine aggregates when the mixed material leaves the conveyor belt and enters the finished product silo. The height difference between the discharge port and the truck bed should be kept within a reasonable range to minimize segregation of coarse and fine aggregates caused by height differences. During transportation, the vehicle speed should not be too high to prevent segregation caused by bumps.
[0112] (3) Spreading of mixture:
[0113] When using a paver for paving, the operator must have proficient technical skills and accurately adjust the process parameters of the paver to ensure that the requirements of flatness, slope, elevation and cross section are met, while minimizing the segregation of materials. The paving steps are as follows:
[0114] ① During paving operations, use a single paver, with longitudinal joints overlapping by 10 cm. After the paver starts and travels 50 meters, use the baseline for paving control, adjust the paving thickness and cross slope, and calibrate the automatic leveling beam. After 50 meters, begin using the leveling beam for paving control. Simultaneously, determine the loose paving coefficient based on the test section and adjust the loose paving thickness and cross slope of the paver.
[0115] ② At least four material transport vehicles must be lined up and waiting in front of the paver. Once loaded, the paver begins paving. The material transport vehicles should always unload 20 to 30 cm in front of the paver, where they will be received and pushed forward by the paver. During the paving process, the number of pauses and bucket retractions of the paver should be minimized.
[0116] ③ A dedicated person must be designated to track and inspect elevation, cross slope and thickness, and to conduct timely verification and adjustments.
[0117] ④ Control the paver's travel speed between 1.5 and 3 m / s to maintain a uniform forward speed during the paving process. It is prohibited to adjust the speed during the operation.
[0118] (4) Rolling:
[0119] The rolling steps are as follows:
[0120] ① Initial Compaction: Use a heavy-duty vibratory roller for static compaction to stabilize and stabilize the mixture. On straight sections and flat curves without superelevation, rolling begins on both sides of the road shoulder and gradually shifts the wheels toward the center. On flat curves with superelevation, rolling begins on the inner shoulder and gradually shifts the wheels toward the outer shoulder. When shifting the wheels, overlap by 1 / 3 of the wheel width each time. After the initial compaction, re-level the surface. At the end of the initial compaction, check the road surface flatness and the cross slope of the road crown, and make adjustments if necessary. ② Re-compacting: Use a heavy-duty vibratory roller for two passes of low-impact vibration and three passes of high-impact vibration. The rolling process should follow the principle of "slow first, fast later, low later, high later, side later center." When shifting the wheels, overlap by 1 / 3 of the wheel width each time. Turning or making sharp turns on a pre-formed gravel layer is strictly prohibited.
[0121] (5) Artificial spreading of machine-made sand:
[0122] After a sufficient number of rollings, a layer of machine-made sand approximately 0.5cm to 1cm thick should be spread over areas where large particles are concentrated due to paving segregation. If conditions permit, a small vibration leveling operation should be performed using a press. Once completed, the road can be opened to traffic.
[0123] (6) Open traffic:
[0124] After completing the artificial spreading of machine-made sand, traffic will be opened for 7 days. Under the action of vehicle load, the mixture will be further compacted, and then the subsequent pavement surface layer construction will be carried out.
[0125] (7) Subsequent construction of pavement surface layer:
[0126] The highway was originally constructed in sections and at different times. The gradation of the cement-stabilized, graded, milled and recycled stone material varied significantly across different sections. The test data listed in Step 2 is from a specific section. During the actual overhaul, the actual particle size of the cement-stabilized, graded, milled and recycled stone material was closely observed, the gradation was frequently tested, and the dosage of the new material for each grade was adjusted.
[0127] In the test work, the new material used four sizes of 0mm-5mm, 5mm-10mm, 10mm-30mm and 30mm-50mm. Due to the small amount of 5mm-10mm, in the actual engineering overhaul, only three sizes of 0mm-5mm, 10mm-30mm and 30mm-50mm were used.
[0128] Although the embodiments of the present invention have been shown and described above, it will be understood that the above embodiments are illustrative and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention.
Claims
1. A method for regenerating recycled materials from cement-stabilized crushed stone layers, characterized in that: The steps include: (1) Grading test: Taking the cement-stabilized crushed stone layer milling and recycling material, screening it and calculating the individual screening rate, cumulative screening rate and passing percentage of the cement-stabilized crushed stone layer milling and recycling material to obtain the gradation of the cement-stabilized crushed stone layer milling and recycling material; Take 30mm-50mm, 10mm-30mm, and 5mm-10mm new crushed stone aggregates, screen them, and calculate the individual screening rate, cumulative screening rate, and passing percentage of the new crushed stone aggregates to obtain the gradation of the new crushed stone aggregates; Taking fine aggregate of 0 mm to 5 mm, screening and calculating the individual screening rate, cumulative screening rate and passing percentage of the fine aggregate to obtain the gradation of the fine aggregate; (2) Preparation of graded recycled mixture: According to the gradation of the cement stabilized crushed stone layer milling recovery material, the gradation of the new crushed stone aggregate and the gradation of the fine aggregate obtained in step (1), the mixed weight ratio of the cement stabilized crushed stone layer milling recovery material, the new crushed stone aggregate and the fine aggregate is calculated until a graded recycled mixture within the target gradation range is obtained.
2. The method for regenerating recycled materials from cement-stabilized crushed stone layer according to claim 1, characterized in that: In the gradation test of step (1), the screening of the cement stabilized crushed stone layer milling recovery material, the screening of the new crushed stone aggregate, and the screening of the fine aggregate all adopt multi-stage screening.
3. The method for regenerating recycled materials from cement-stabilized crushed stone layer according to claim 2, characterized in that: The sieve specifications used in the multi-stage screening include 0.075mm standard sieve, 0.3mm standard sieve, 0.6mm standard sieve, 1.18mm standard sieve, 2.36mm standard sieve, 4.75mm standard sieve, 9.5mm standard sieve, 13.2mm standard sieve, 16mm standard sieve, 19mm standard sieve, 26.5mm standard sieve, 31.5mm standard sieve, 37.5mm standard sieve and 53mm standard sieve.
4. The method for regenerating recycled materials from cement-stabilized crushed stone layer according to claim 1, characterized in that: Step (2) includes the following specific steps: (2-1) calculating the mixing weight ratio of the cement-stabilized crushed stone layer milling recycled material, the new crushed stone aggregate and the fine aggregate according to the target gradation range, the gradation of the cement-stabilized crushed stone layer milling recycled material, the new crushed stone aggregate and the fine aggregate to obtain a graded recycled mixture; (2-2) performing multi-stage screening on the graded recycled mixture obtained in (2-1), calculating the individual screening rate, cumulative screening rate and passing percentage of the graded recycled mixture, and obtaining the gradation of the graded recycled mixture; (2-3) If the gradation of the graded recycled mixture is within the target gradation range, it means that the preparation of the graded recycled mixture is qualified; if the gradation of the graded recycled mixture is not within the target gradation range, repeat steps (2-1) and (2-3) until a graded recycled mixture within the target gradation range is obtained.
5. The method for regenerating recycled materials from cement-stabilized crushed stone layer according to claim 4, characterized in that: The mass percentages of the graded recycled mixture within the target gradation range passing through the sieve holes are as follows: 53mm sieve hole 100%, 37.5mm sieve hole 75%-98%, 19mm sieve hole 40%-60%, 9.5mm sieve hole 25%-40%, 4.75mm sieve hole 20%-35%, 2.36mm sieve hole 15%-25%, 0.6mm sieve hole 5%-10%, and 0.075mm sieve hole 0%-5%.
6. Graded recycled mixture, characterized in that: The method is prepared by the regeneration method according to any one of claims 1 to 5.
7. The graded recycled mixture according to claim 6, characterized in that: The maximum nominal particle size of the graded recycled mixture is 53 mm.
8. The graded recycled mixture according to claim 6, characterized in that: The fine aggregate of 0mm-5mm in the graded recycled mixture accounts for 10%-20% of the weight content of the graded recycled mixture; The graded recycled mixture also includes cement; the cement accounts for 2%-2.5% of the weight content of the graded recycled mixture.
9. Application of graded recycled mixture, characterized in that: The graded recycled mixture described in any one of claims 6 to 8 is used as the pavement base and pavement subbase of a newly built road.
10. The use of the graded recycled mixed material according to claim 9, characterized in that: The moisture content of the graded recycled mixture is increased by 2% based on the optimal moisture content.
Citation Information
Patent Citations
Ultra-thickness reclaimed material cement stabilized macadam paving, vibrating and stirring construction technology
CN110284409A
Grading composition design method of large-particle-size graded broken stone
CN111339680A
Cement-improved skeleton interlocking type large-particle-size graded broken stone base layer suitable for heavy traffic
CN117623688A
Old asphalt concrete recycling and collecting method, recycled aggregate, preparation method and application
CN118639489A
Environment-friendly high-dosage RAP regenerated cement stabilized macadam mixture and preparation method thereof
CN118771805A